Water mass structure determine the prokaryotic community and metabolic pattern in the Korea Strait during fall 2018 and 2019 - Thangaraj, Satheeswaran; Kim, Hyo-Ryeon; Kim, Seo-Young; Jung, Hae-Kun; Kim, Ju-Hyoung; Kim, Il-Nam (Frontiers in Marine Science, 2023)
The Korea Strait (KS) is a crucial marine passage for transporting heat, salt, and materials from the South Sea to the East Sea. The Tsushima Warm Water (TWW) and Korea Strait Bottom Cold Water (KSBCW) are major water masses that flow across the strait, but their effects on prokaryotic communities have been unclear. We used high-throughput sequencing to study the impact of TWW and KSBCW on prokaryotic composition and metabolic changes in the upper (0–50m; UL), middle (50–75m; ML), and bottom (75–150m; BL) layers during the fall of 2018 and 2019. The results showed that the UL had a freshwater influence from Changjiang Diluted Water in 2019, altering prokaryotic compositions and metabolic potentials. The KSBCW in the BL transported new bacterial communities with unique metabolic characteristics. Key genes involved in carbon metabolism had water mass impacts, preferring lower saline and temperature environments, and carbon fixation potential shifted from phototrophs in 2018 to chemotrophs in 2019. Temperature changes induced acclimation processes producing heat- and cold-shock genes/proteins. Our findings indicate that the freshwater influence and KSBCW modified the prokaryotic composition and metabolic function differentially. These results are important in understanding the relationship between water masses and ongoing environmental changes in this understudied region.